Journal of local government research and innovation JOLGRI. (AOSIS, 2020)
"The Journal of Local Government Research and Innovation (JOLGRI) seeks to publish and foster knowledge development in educational, epistemological and practice advancements within local government that will result in alternative models practised in local government service delivery and governance"--